AN ECONOMIC ANALYSIS OF TOBACCO PROCESSING INDUSTRY IN WESTERN AND KWARA STATES OF NIGERIA (1978)
The objective of this study is to assess the economic performance of tobacco processing industry in Western and Kwara States of Nigeria. After a brief discussion of the development of tobacco industry in Nigeria, some technical aspects of tobacco leaf production, cigarettes manufacture, and blackfat manufacture were discussed. Three firms were selected for the study. These are Nigerian Tobacco Company Limited, Philip Morris (Nigeria) Limited and Premier Tobacco Company Limited. The data used for the study were obtained from two main sources. The Federal Office of Statistics, Lagos; and through questionnaires and personal interviews with the selected tobacco processing firms. Investigations on the economic characteristics of the selected firms indicated that the firms differed not only in year of establishment, but also in ownership patterns (private vs. quasi government), size of capital, labour employment; output size, and value-added to the Nigerian economy. The largest firm (NTC), employed 3,302 workers in 1973 whilst Philip Morris (Nigeria) Limited, which is a medium-sized firm, employed 836 workers during the same period. The smallest firm, Premier Tobacco Company, employed only 40 workers during the same year. Also in terms of capital investment, NTC invested N15,000,000 in 1973, Philip Morris invested N2,400,604, and Premier Tobacco Company invested only N746,150 during the same period. In terms of value-added, NTC contributed N21,4l5,604 whilst Philip Morris added N6,582,75C and PTC added only N33,350 to the economy for the year 1973. The analysis of costs and returns involved in cigarettes manufacture revealed considerable disparity in the cost outlay and in the net returns to each firm. In 1973, for instance, the total cost for NTC was N31,387,419; that of Philip Morris was N10,l30,457; while that of PTC was only NI02.877. The net returns were Ml8,387,581 for NTC, «5,3l3,8o4 for Philip Morris and Nl4,346 for PTC for the same period. From the balance sheets and income statements of these firms, a financial analysis was carried out. This analysis revealed some favourable liquidity and solvency ratios for each firm and thus, each firm could easily qualify for loans advancement from financial institutions for the period under review. Using some time series data collected from the firms, production functions for tobacco processing industry were estimated. The estimated functions revealed that the level of productivities of tobacco leaf input, labour, and capital inputs varied from one firm to the other whilst excise tax had some negative effects on cigarettes manufacture. The sum of elasticity coefficients (which was less than one) implied a decreasing return to scale. The policy implication of the study stressed the need to check smuggling of cigarettes into the country from the neighbouring countries and the need for expansion and better management of the cigarette firms.